1992
DOI: 10.1073/pnas.89.21.10114
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length predicts replicative capacity of human fibroblasts.

Abstract: When human fibroblasts from different donors are grown in vitro, only a small fraction of the variation in their finite replicative capacity is explae by the chronological age of the donor. Because we had previously shown that telomeres, the terminal guanine-rich sequences of chromosomes, shorten throughout the life-span of cultured cells, we wished to determine whether variation in initial telomere length would account for the unexplained variation in replicative capacity. Analysis of cells from 31 donors (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
1,264
5
11

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,978 publications
(1,333 citation statements)
references
References 40 publications
53
1,264
5
11
Order By: Relevance
“…As a mean (7.53), they did not differ from that of the two controls (6.970.2 and 7.470.3), and all telomere sizes kept within the range of normal values (6.5-8.5), as published. [42][43][44] Number of D4Z4 repeats…”
Section: Telomere Sizementioning
confidence: 99%
“…As a mean (7.53), they did not differ from that of the two controls (6.970.2 and 7.470.3), and all telomere sizes kept within the range of normal values (6.5-8.5), as published. [42][43][44] Number of D4Z4 repeats…”
Section: Telomere Sizementioning
confidence: 99%
“…2,6 Since telomerase activity is absent in most somatic cells, telomere shortening occurs in these cells. [7][8][9][10] In contrast, immortal tumor cell lines and germ cell tissues show high levels of telomerase activity, resulting in a stable telomere length and unlimited proliferation. 7,11 It was recently reported that human hematopoietic stem/progenitor cells and activated lymphocytes exhibit low levels of telomerase activity.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In contrast, immortal tumor cell lines and germ cell tissues show high levels of telomerase activity, resulting in a stable telomere length and unlimited proliferation. 7,11 It was recently reported that human hematopoietic stem/progenitor cells and activated lymphocytes exhibit low levels of telomerase activity. [12][13][14] However, telomere shortening is observed in these cells, implying that the level of activity is insufficient to maintain stable telomere length and that the proliferative potential of these cells is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The telomere hypothesis is generally accepted as the explanation for the mechanism that underlies cell senescence (26,27). Structures of telomeres, the terminal, guanine-rich sequences of chromosomes (TTAGGG repeats in humans and other vertebrates), work to stabilize the chromosome during replication by protecting the chromosome end against exonucleases.…”
Section: Discussionmentioning
confidence: 99%
“…Structures of telomeres, the terminal, guanine-rich sequences of chromosomes (TTAGGG repeats in humans and other vertebrates), work to stabilize the chromosome during replication by protecting the chromosome end against exonucleases. Telomere length decreases with replication, and when this has decreased to a critical length, the cell is signaled to stop dividing and to enter cellular senescence (replicative senescence) (26,27). Telomerase is an RNAdependent DNA polymerase that synthesizes telomeric DNA sequences.…”
Section: Discussionmentioning
confidence: 99%